2012
DOI: 10.4073/csr.2012.9
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to reduce the prevalence of female genital mutilation/cutting in African countries

Abstract: This Campbell systematic review examines the empirical research on the effectiveness of female genital mutilation/cutting (‘FGM/C’) interventions to reduce the occurrence of FGM/C practices in the 28 African countries that carry out FGM/C practices. The review also examines the empirical research on contextual factors that may help explain the effectiveness, or lack thereof, of such interventions. It summarises findings from 8 effectiveness studies and 27 context studies conducted in seven different African co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 109 publications
3
60
0
2
Order By: Relevance
“…Two recent systematic reviews by Berg, Denison and colleagues have identified a total of just eight evaluations of interventions that included before and after assessments and a control or comparator group (Berg et al, 2009;Berg & Denison, 2013). None of these evaluations assessed interventions delivered in a European context.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent systematic reviews by Berg, Denison and colleagues have identified a total of just eight evaluations of interventions that included before and after assessments and a control or comparator group (Berg et al, 2009;Berg & Denison, 2013). None of these evaluations assessed interventions delivered in a European context.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the search should be clearly documented (Moher et al 2009). Figure 1 presents an example search flow from a review on interventions to reduce incidence of female genital mutilation and cutting (Berg and Denison 2012). A typical review goes from several thousand or so papers identified in the initial search (often many more in social science literature), to just a couple of hundred for which an abstract or full-text screening review is conducted, and then a dozen or less included effectiveness studies.…”
Section: Setting the Questionmentioning
confidence: 99%
“…And this evidence is thin in studies that are included because of rigorous impact evaluation designs. Hence, there is a need to turn to evidence in the other studies excluded at that final stage, as shown in the additional context studies included in Berg and Denison (2012). However, there is not yet agreement as to what constitutes credible evidence to allow additional studies to be included for this purpose (see Snilstveit 2012).…”
Section: Setting the Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sin embargo, si se considera el total de revisiones hechas sobre temas que atañen a la educación en colaboración con otros grupos, la cifra asciende a 91 revisiones sistemáticas publicadas, sobre temas tan diversos como la importancia del involucramiento de las familias en el logro académico de los estudiantes (Nye, Schwartz y Turner, 2006;Spier et al, 2013), o la efectividad de los programas de intervención sobre el acoso escolar (Farrington y Ttofi, 2009;Ttofi, Loeber, Lösel, y Farrington, 2012), la violencia (Petrosino, Guckenburg, y Fronius, 2013) o el abuso sexual (Zwi et al, 2007), entre otras. Muchas de las revisiones tratan sobre temas en extremo específicos, como pueden ser la efectividad de los programas educativos para la reducción de la prevalencia de la mutilación genital femenina en paí-ses africanos (Berg y Denison, 2012), o de los programas para disminuir el embarazo en adolescentes (Scher, Maynard, y Stagner, 2006) o de los programas de bolsa de empleo para personas con desórdenes del espectro autista (Westbrook, Fong, Nye, Williams, Wendt y Cortopassi, 2013).…”
Section: La Institucionalización De La Educación Basada En La Evidenciaunclassified